2018
DOI: 10.1088/1361-6463/aaa30f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dielectric liquid rise between parallel electrodes under capillary and dielectrophoretic forces

Abstract: An electric field can affect a dielectric fluid flow and this effect can be used especially in micro-devices. A differential second order equation for a temporal dependence of the liquid height-of-rise in a microchannel made of two parallel plates is modified to account for a liquid dielectrophoretic (LDEP) force, which is a result of an electric field occurring between the plates. This equation takes into account capillary, LDEP, inertial and gravitational forces for viscous, incompressible fluid. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…This has been demonstrated before ,, through electrowetting via different approaches. Lackowski et al illustrated this by including a contact line resistance in their analysis. Wang and Jones used Maxwell’s stress tensor in combination with electrical circuit analysis to investigate electrowetting and its effects on the height rise of various solutions. , Hong et al looked at the time response of the electrowetting effect on height rise using an overdrive voltage.…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated before ,, through electrowetting via different approaches. Lackowski et al illustrated this by including a contact line resistance in their analysis. Wang and Jones used Maxwell’s stress tensor in combination with electrical circuit analysis to investigate electrowetting and its effects on the height rise of various solutions. , Hong et al looked at the time response of the electrowetting effect on height rise using an overdrive voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The electromechanical approach of electrowetting explains the dipole water molecule’s charge dynamics and electric field concentration in electrowetting. Several studies [ 17 , 18 , 19 , 20 ] have used this approach and associated equations to explain electrowetting phenomena. In this study, we also used the same approach and related equations.…”
Section: Theoretical Background On Dipole Water Molecule’s Charge Dyn...mentioning
confidence: 99%
“…Chen et al [34] realized the liquid transportation and created a droplet containing a single bead by LDEP. Lackowski and Nowakowska [35] showed that isopropanol (2-propanol, C 3 H 8 O) was suitable for presenting LDEP effect in capillary systems and analyzed the influence of the LDEP force on a temporal dependence of the liquid height-of-rise.…”
Section: Programmable Liquid Matter Via External Fieldmentioning
confidence: 99%